Markers of Apoptosis: Methods for Elucidating the Mechanism of Apoptotic Cell Death from the Nervous System - Paul G. Smyth; Stephen A. Berman; Sherry Bursztajn (BioTechniques)
Apoptosis is a highly conserved energy-requiring program for non-inflammatory cell death that is important in both normal physiology and disease. Numerous techniques have been used to study apoptosis. In the nervous system, apoptosis is necessary for normal development, but it also occurs in many acute and chronic pathologic conditions. This review places commonly used markers of apoptosis and their detection in the context of what is now known about the process of apoptosis. We review the potential role of apoptosis in nervous system and neurodegenerative disorders (Alzheimer’s disease, Parkinson’s disease, and amyotrophic lateral sclerosis). We then describe important morphological, immunocytochemical, and molecular genetic markers for apoptosis, including proteases, signal transduction molecules, and mitochondrial proteins. The possibility of manipulating apoptosis therapeutically in conditions of too many or too few cells is under active investigation.